2010
DOI: 10.1016/j.jri.2009.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor-inducible 14 (Fn14) is expressed in the lower genital tract and may play a role in amplifying inflammation during infection

Abstract: TNF-like weak inducer of apoptosis (TWEAK) is a member of the tumor necrosis factor (TNF) cytokine superfamily which regulates a number of cellular responses, including inflammation and proliferation. TWEAK is primarily secreted by phagocytic cells and its receptor, fibroblast growth factor-inducible 14 (Fn14), is expressed on non-lymphoid cells, including epithelial, endothelial and mesenchymal cells. The TWEAK/Fn14 pathway is highly conserved from an evolutionary standpoint, and has been shown to play a role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…TWEAK cooperates with IL-17 to augment inflammatory mediator expression in HeLa cells (T. Hamilton, personal communication, January 16, 2009), analogous to the cooperation between TNF-␣ and IL-17 [69]. TWEAK also potentiates the pro-inflammatory effects of TLR ligands, synergizing with Pam 3 CysSK 4 for the stimulation of IL-8 production by epithelial cells [70] and with oxidized-LDL for the production of MCP-1 and RANTES by vascular smooth muscle cells and a renal proximal tubule cell line [71]. In addition, TWEAK-induced RANTES was synergistically augmented by TGF-␤ in human keratinocyte cultures [31].…”
Section: General Role Of Tweak/fn14 In Inflammatory Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…TWEAK cooperates with IL-17 to augment inflammatory mediator expression in HeLa cells (T. Hamilton, personal communication, January 16, 2009), analogous to the cooperation between TNF-␣ and IL-17 [69]. TWEAK also potentiates the pro-inflammatory effects of TLR ligands, synergizing with Pam 3 CysSK 4 for the stimulation of IL-8 production by epithelial cells [70] and with oxidized-LDL for the production of MCP-1 and RANTES by vascular smooth muscle cells and a renal proximal tubule cell line [71]. In addition, TWEAK-induced RANTES was synergistically augmented by TGF-␤ in human keratinocyte cultures [31].…”
Section: General Role Of Tweak/fn14 In Inflammatory Responsesmentioning
confidence: 99%
“…The ability of bacterial components and inflammatory cytokines to induce the expression of Fn14 is another important aspect of the feed-forward loop, promoting the accumulation of immune effector cells and substances. In addition, it has been reported that TWEAK augments stimulation with TLR ligands, synergizing with Pam 3 CysSK 4 for stimulation of IL-8 production in the case of urogenital epithelial cells [70]. Further, TWEAK cooperates with IL-17, an inflammatory cytokine up-regulated in CD, to augument inflammatory mediator expression in Hela cells (T. Hamilton, personal communication, January 16, 2009), analogous to the cooperation between TNF-␣ and IL-17 [69,105].…”
Section: Chronic Inflammationmentioning
confidence: 99%
“…However, regulation of Fn14 expression in the genital tract in general remains unclear. Although hormonal signals are unlikely to be required for Fn14 receptor expression on the genital tract epithelial cells as reported previously, regulation of Fn14 receptor expression by hormonal changes is still a possibility. In the present study, distinct effects of E 2 and/or P 4 on the regulation of both Fn14 mRNA and protein expression by goat EECs were observed in the presence and absence of ESCs.…”
Section: Discussionmentioning
confidence: 67%
“…On top of this, they must maintain the ability to respond to pathogenic microorganisms and other dangers that might be encountered at this site. A number of in vitro and in vivo studies suggest that the TWEAK/Fn14 interaction may play a role in regulating inflammation within tissues . Given its reported effects on cell proliferation and cell survival, TWEAK/Fn14 axis may be also play a role in response to cyclic hormonal changes, during pregnancy, and other physiologic conditions .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation